Urban sustainability through strategic planning: A case of metropolitan planning in Khulna city, Bangladesh - Md. Ashiq Ur Rahman (Journal of Urban Management, 2016)
Planning is a crucial element for any development initiative. Planning entails choice making in pursuit of stated goals e.g. improving living conditions for individuals and societies. Planning initiatives are employed within social systems that are governed by institution, and planning intervenes with and may reconfigure these institutions resulting in social change. This paper discusses how urban sustainability can be achieved through strategic action in urban development by analysing the planning process of Khulna city, Bangladesh. This paper reviews different scholarly articles to draw a conceptual framework for identifying the interface of strategic planning, components of strategic action planning and urban sustainability. Based on this conceptual framework this paper identifies the scope of achieving urban sustainability through analysing the current planning practice of Khulna city, Bangladesh. This paper identifies that though the Khulna city plan adopted the approach of strategic planning but it failed to comply with its theoretical notion to achieve the issues related to urban sustainability. Analysis reveals that in terms of social attribute that recognizes the interest of different group of people the exiting planning packages is not sustainable. Similar phenomenon have been observed in terms of recognition of gender and marginalized people in planning, equitable provision of income and employment generation, peoples' participation in planning and polices for ensuring equitable access to infrastructure services. Therefore the existing planning package of Khulna city failed to achieve the issues of urban sustainability through its adapted strategic planning approach.
Keywords: 710; Khulna; Participation; Social justice; Strategic planning; Sustainability